Índice de propensão ao desenvolvimento sustentável: o nordeste brasileiro - Leite, Tércio Sobral Cavalcante (2013)
This study aims to analyze comparatively the hierarchical and spatial distribution of the Propensity Score Sustainable Development, states in the Northeast of Brazil. To do so, we employ the theoretical postulates of Brito (2004) and Leal (2008) about quality of life, covering a brief history of its emergence and difficult definition of the term, the studies of Van Bellen (2005), Moretto and Giacchini (2006 ), Veiga (2006) Malheiros et al (2008) and Oliveira (2009) about sustainable development, its appearance, concept and measurement. In order to analyze the Propensity Index of Sustainable Development, of the states in the Northeast of Brazil, we used the same dimensions adopted by IBGE to measure this index, namely environmental, social, economic and institutional. The database of variables used was IBGE, PNAD, MDS, BCB and MDIC. The choice of these took into account 03 (three) criteria: data reliability, data availability and federative unit level consistent with the theme. The procedure was also performed to standardize in view of the data are in separate units. Then, the states were ranked in relation to both IPDS, as compared to the indices of each dimension. Thus, was verified, the contribution of each variable for each indicator, each indicator for each dimension and each dimension for IPDS. Then were realized several interpretations, including identifying (s) variable (s) and indicator (s) that most impacted (plow) in the result. Our analysis allowed us to observe that, among the states in the Northeast, the state of Sergipe showed greater propensity to sustainable development and Maranhão was the state that had lower propensity to sustainable development. It was also evident that there is difference in the propensity intervals sustainable development among the northeastern states.